Perfil da distribuição e custos dos medicamentos do componente especializado da assistência farmacêutica para doença de Alzheimer no estado do Ceará - Pontes, Francisco José Oliveira de (2015)
Alzheimer's disease is an important cause of loss of functionality and increase in direct and in direct costs worldwide. As the disease progresses to more severe forms, it becomes more prominent the cholinergic deficit in co rtical areas, that is one of the targets of drug therapy with acetylchol inesterase inhibitors. In 2002, the Brazilian government created the Program of Assistance to patients with Alzheimer ́s Disease . The objective of this study is to characterize the distri bution and costs of the Specialized Component of the Pharmaceutical Assistance for Alzheimer Disease in the state of Ceará. Methodology: This is a descriptive study that used secondary data about the distribution of high - cost drugs from Pharmaceutic al Care Coordination Ceará – of the State Health Secretariat COASF - SESA and HORUS System. Program costs with anticholinesterasics were evaluated from 2002 - 2013 , the profile of gender, age and type of medication used by patients with active registration in May 2015 were also analysed . Results: In May 20 15, 5,403 patients were register ed in the program for the period of 90 days to receive cholinesterase inhibitors. 3,791 (70%) were female. The age group 70 to 79 years and 80 to 89 years had the highest number of patients, 39 % and 43 %, respectively. The average age was 79.4 years (SD = 9.56) . We estimated to 25.36% the coverage of the distribution of drugs by the program . Most patients (55%) use d donepezil and Fortaleza remained as the main anticholinesterase d istribution center in the state from 2002 to 2013. F rom 2002 the cost s have risen up to 8 million reais in 2010 . Since then, the amount spent with the distribution of drugs has been reduced gradual ly, reaching 3.8 million reais in 2013. In total, it was sp ent 53 million reais in distribution of anticholinesterasics from 2002 to 2013. Conclusion: the distribution of anticholinesterasics in Ceará , despite the growth in recent years, maintains a low coverage, centered on the state capital.